Dichloromethane stem bark extract of Goniothalamus lanceolatus Miq. modulates inflammatory cytokines and ameliorates tissue damage in Plasmodium berghei-infected mice - Rozaini Mohd Zohdi, Fatin Amelina Kaharudin, Shahida Muhamad Mukhtar, Hasidah Mohd Sidek, Nor Hadiani Ismail (Journal of Applied Pharmaceutical Science, 2022)
Goniothalamus lanceolatus Miq. has been reported to possess in vivo antiplasmodial activity with dichloromethane (DCM) stem bark extract identified as the most active extract. This study investigated the therapeutic role of the DCM stem bark extract of G. lanceolatus in modulating inflammatory cytokines in Plasmodium berghei-infected mice and ameliorating tissue damage caused by the infection. Infected BALB/c mice were randomly divided into three groups. Groups I, II, and III were intraperitoneally treated with the DCM stem bark extract (30 mg/kg bwt), chloroquine (1 mg/kg bwt), and Tween 60 (0.2 ml/kg bwt), respectively. On day 8 after infection, mice were sacrificed, blood was collected for the measurement of cytokines, and the livers and spleens were harvested for histopathological examination. The extract modulated the host immune response by significantly (p < 0.05) decreasing the plasma levels of interleukin (IL)-1α, IL-1β, IL-6, and interferon-γ during malarial infection. Accordingly, mice treated with the extract showed marked improvements in hepatocellular structure and better preservation in splenic histoarchitecture. This study indicates that the DCM stem bark extract exerts its therapeutic role in the malaria-infected host by reducing proinflammatory cytokines and ameliorating tissue damage associated with the infection. This suggests that the extract may serve as a promising adjunct therapy for malaria. However, further dose-response studies are required to determine the optimal dose of the extract and provide a deeper understanding of its therapeutic potential.
Keywords: Goniothalamus lanceolatus, Plasmodium berghei, inflammatory cytokine, histopathology, malaria